2014
DOI: 10.2505/4/jcst14_043_04_48
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition: An Effective Tool to Promote Success in College Science Learning

Abstract: Metacognition has been shown to lead to deeper, more durable, and more transferable learning (Bransford, Brown, & Cocking, 2000). This article describes a case study in which metacognition was introduced to undergraduate science (chemistry) classrooms. Students came to understand the difference between superficial memorization and real learning through specific classroom interventions, which were also designed to help students develop metacognitive learning strategies. The aim of the study was to instruct educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 18 publications
5
74
2
Order By: Relevance
“…Metacognitive strategy were the most effective one in enhancing academic achievement and be integrated in the classroom so as to help students learn material more efficiently, retain information longer and generalize skills. 6 Implementation of metacognitive strategies contributed to the increase of learning and curricula 23 . According to previous studies at the intermediate level, problem-based learning (PBL) shows effective results in increasing metacognitive knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Metacognitive strategy were the most effective one in enhancing academic achievement and be integrated in the classroom so as to help students learn material more efficiently, retain information longer and generalize skills. 6 Implementation of metacognitive strategies contributed to the increase of learning and curricula 23 . According to previous studies at the intermediate level, problem-based learning (PBL) shows effective results in increasing metacognitive knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these practices are needed to evaluate scientific claims made in the popular media. A case study by Zhao, Wardeska, McGuire and Cook (2014) on learning chemistry concluded that by introducing metacognition in learning through specific classroom interventions that were designed to help students develop metacognitive learning strategies, the students came to understand the difference between superficial memorization and real learning.…”
Section: Discussionmentioning
confidence: 99%
“…Distributed practice Implementing a schedule of practice that spreads out study activities over time 10. Interleaved practice Implementing a schedule of practice that mixes different kinds of problems, or a schedule of study that mixes different kinds of material, within a single study session Another condition for success in learning, especially in the academic one, is the capitalization of metacognition, of personal reflection (Mogonea & Ştefan, 2014, Zhao, Wardeska, McGuire, Cook, 2014, Mogonea, 2014, of cognitive flexibility, of autonomy in learning (Kormos & Csizér, 2014, Ştefan, 2014, of cognitive and socio-cognitive conflicts (Mogonea & Popescu, 2015). In addition to the metacognitive dimension, equally important is the non-cognitive dimension of personality, which often makes the difference between a successful or unsuccessful learning activity (Ștefan & Mogonea, 2015).…”
Section: Theoretical Foundationmentioning
confidence: 99%